THE APPLICATION OF ICE BREAKING ACTIVITIES IN ENGLISH TEACHING FOR JUNIOR HIGH SCHOOL STUDENTS IN MTSN 11 AGAM - Oktavia Elya Zahra; Veni Roza; Ahsanul Husna (CV. ADIBA AISHA AMIRA, 2023)
The journal entitled